Positive electrode active material and preparation method thereof, sodium ion battery and electric equipment

By adopting the structure of the kernel-first shell-second shell layer in the positive electrode material of sodium ion battery, the performance of existing materials in sodium ion batteries has been solved, and higher battery performance and material stability are realized. Essence

CN119361664AActive Publication Date: 2025-01-24NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD

Patent Information

Application Number
CN202411931767.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-01-24
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The existing sodium-electric layered positive electrode materials have low first discharge capacity, rate performance and cycle performance in sodium ion batteries, and poor material stability.

Method used

The structural design of core-first shell-second shell is adopted. The core is a sodium-poor phase material with a sodium content of 0.75~0.85, and the first shell is a sodium-rich phase material with a sodium content of 0.85~0.95. Doped with B element, the second shell layer is an inorganic metal oxide layer.

Benefits of technology

Improve the first discharge capacity, storage performance, cycle performance and magnification performance of sodium ion batteries, and enhance the stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361664A_ABST
    Figure CN119361664A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode active material and a preparation method thereof, a sodium ion battery and electric equipment, and belongs to the technical field of positive electrode active material manufacturing. The positive electrode active material comprises an inner core, a first shell layer and a second shell layer. The material of the inner core comprises Naa1Nib1Fec1Mnd1O2, and a1 is more than or equal to 0.75 and less than or equal to 0.85; the first shell layer is further doped with an element B, the material of the first shell layer comprises Naa2Nib2Fec2Mnd2BfO2, a2 is larger than or equal to 0.85 and smaller than or equal to 0.95, and a2 is not equal to a1; and the second shell layer is an inorganic metal oxide layer. The sodium ion battery prepared from the positive electrode active material has relatively high first discharge capacity and relatively excellent storage performance, cycle performance and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of positive electrode active material manufacturing, and in particular to a positive electrode active material and a preparation method thereof, a sodium ion battery and an electrical device. Background Art

[0002] In the prior art, sodium-based layered cathode materials have attracted more and more attention due to their advantages of low cost and excellent high and low temperature performance. Among them, the P2 phase layered cathode material is a sodium-poor phase, and its corresponding battery has relatively excellent storage performance, but the first discharge capacity and rate performance of the prepared sodium-ion battery are low; in order to improve the first discharge capacity and rate performance of its corresponding battery, the O3 phase cathode active material (the sodium content is higher than the P2 phase, which is a sodium-rich phase material) is selected to be coated on the outside of the P2 phase. However, the O3 phase material has the problem of poor cycle performance of the corresponding battery due to its poor material stability. Therefore, it is urgent to develop a new sodium-based layered cathode material so that the corresponding battery can have a relatively high first discharge capacity, relatively excellent storage performance, cycle performance and rate performance. Summary of the invention

[0003] The purpose of the present application is to provide a positive electrode active material and a preparation method thereof, a sodium ion battery and an electrical device. The sodium ion battery prepared from the positive electrode active material has a high initial discharge capacity, relatively excellent storage performance, cycle performance and rate performance.

[0004] The embodiment of the present application is implemented as follows: In a first aspect, the present invention provides a positive electrode active material, including a core, a first shell layer, and a second shell layer. The core material includes: Na a1 Ni b1 Fe c1 Mn d1 O2, 0.75≤a1≤0.85; the first shell is coated outside the inner core, and the first shell is also doped with B element. The materials of the first shell include: Na a2 Ni b2 Fe c2 Mn d2 B f O2, 0.85≤a2≤0.95, and a2 is not equal to a1; the second shell layer is coated on the outside of the first shell layer, and the second shell layer is an inorganic metal oxide layer.

[0005] In the present application, the positive electrode active material has the above-mentioned specific structure, specifically, the inner core includes a sodium-poor phase material with a sodium content of 0.75~0.85, and the outer core is coated with a first shell layer (including a sodium-rich phase material with a sodium content of 0.85~0.95) and a second shell layer in sequence, and the first shell layer is also doped with B element, wherein the sodium-poor inner core material enables the corresponding battery to have relatively excellent storage performance, and the coating of the first shell layer helps to improve the first discharge capacity and rate performance of the corresponding battery, and the doping of the B element and the coating of the second shell layer help to improve the material stability of the first shell layer, so that the corresponding battery has relatively excellent cycle performance. Therefore, the sodium ion battery prepared by the positive electrode active material provided in the embodiment of the present application has both a high first discharge capacity, relatively excellent storage performance, cycle performance and rate performance.

[0006] In some optional embodiments, the material of the inner core further satisfies: 0.20≤b1≤0.35, 0.20≤c1≤0.40, 0.20≤d1≤0.40, and b1+c1+d1=1; the material of the first shell further satisfies: 0.20≤c2≤0.40, 0.20≤d2≤0.40, 0.0001≤f≤0.01, and b2+c2+d2=1; the material of the second shell includes: Na a3 XO b3 , a3 is equal to a2, 1≤b3≤4, and X is selected from at least one of Mg, Al, Sr, Zr, Ti and Y.

[0007] In the above technical solution, the material of the core and the material of the first shell are limited to a more suitable range, so that the corresponding battery can have a higher first discharge capacity, better storage performance, cycle performance and rate performance. In addition, the metal elements other than sodium in the second shell are selected as the above elements, which are helpful for the formation of the interface film during the charge and discharge process of the corresponding battery, thereby helping to improve the storage performance and cycle performance of the corresponding battery.

[0008] In some optional embodiments, X is selected from at least one of Zr and Y.

[0009] In the above technical solution, the element of X is selected as Zr and / or Y, which is more conducive to the formation of the interface film of the corresponding battery during the charging and discharging process, thereby being more conducive to improving the storage performance and cycle performance of the corresponding battery.

[0010] In some optional embodiments, the BET of the positive electrode active material is 0.34-0.44 m 2 / g, and the Dv3 of the positive electrode active material is 2.3~3.2 μm.

[0011] In the above technical solution, the BET and Dv3 of the positive electrode active material are both within a relatively suitable range, indicating that the material has a relatively suitable particle size and contains less fine powder, thereby improving the cycle performance of the battery.

[0012] In some optional embodiments, in the positive electrode active material, the doping depth is greater than 0.3 μm, and the mass percentage of the B element is less than 0.005%; the doping depth is equal to 0.1 μm, and the mass percentage of the B element is greater than 0.02%.

[0013] In the above technical solution, limiting the content of the B element at different doping depths within a specific range helps to further improve the material stability of the material, thereby making the corresponding battery have better cycle performance.

[0014] In a second aspect, an embodiment of the present application provides a method for preparing a positive electrode active material, comprising the following steps: mixing raw materials containing Ni, Fe, Mn and a first Na source to obtain a first mixture; wherein, in the first mixture, the ratio of the total molar amount of Ni, Fe and Mn to the molar amount of Na is 1:(0.75~0.85); performing a first-stage sintering on the first mixture to obtain an inner core; mixing the inner core with a second Na source to obtain a second mixture; wherein, in the second mixture, the ratio of the total molar amount of Ni, Fe and Mn to the molar amount of Na is 1:(0.85~0.95); performing a second-stage sintering on the second mixture to obtain a positive electrode material intermediate; mixing the positive electrode material intermediate, boric acid and a metal source to obtain a third mixture; performing a third-stage sintering and a fourth-stage sintering on the third mixture in sequence, wherein the treatment temperature of the fourth-stage sintering is higher than the treatment temperature of the third-stage sintering, to obtain a positive electrode active material.

[0015] In the above technical scheme, on the one hand, in the process of preparing the positive electrode active material, the ratio of the total molar amount of Ni, Fe and Mn in the first mixture to the molar amount of Na is limited to the range of 1: (0.75~0.85), and the ratio of the total molar amount of Ni, Fe and Mn in the second mixture to the molar amount of Na is limited to the range of 1: (0.85~0.95), so as to prepare a positive electrode active material intermediate with a core-shell structure with a sodium-poor phase inside and a sodium-rich phase outside, so that the corresponding battery has relatively excellent storage performance, first discharge capacity and rate performance; at the same time, the inner core of the sodium-poor phase has a first shell layer of a sodium-rich phase (the sodium-rich phase is more active than the sodium-poor phase), which is conducive to the formation of the second shell layer in the subsequent sintering process (it is easier to form a coating layer and the formed coating layer is more uniform, thereby increasing the structural strength of the material, so that the material is not easy to form small particles in the subsequent crushing process), so that the prepared positive electrode active material has the advantage of less fine powder. On the other hand, the third mixture contains boric acid in addition to the positive electrode material intermediate and the metal source. With the help of the fluidity of boric acid, a relatively uniform inorganic metal oxide layer can be formed during the third stage sintering process, thereby improving the uniformity of the inorganic metal oxide layer coating the positive electrode material intermediate, thereby reducing the amount of alkali on the surface of the material and helping to improve the stability of the material, so that the corresponding battery has a relatively excellent cycle performance. At the same time, the relatively uniform coating layer can also make the prepared positive electrode active material have the advantage of less fine powder; in addition, after the fourth stage sintering at a higher temperature, the B element can be further doped from the surface of the material into the material, and the further doping of the B element also helps to improve the stability of the material, so that the corresponding battery has a relatively excellent cycle performance. Through the combined effect of the two aspects, the prepared positive electrode active material has the advantages of less fine powder, lower alkali on the surface of the material and higher material stability, so that the prepared sodium ion battery has both a higher first discharge capacity, relatively excellent storage performance, cycle performance and rate performance.

[0016] In some optional embodiments, in the first mixture, the molar ratios of Ni, Fe and Mn are (0.2~0.35):(0.2~0.4):(0.2~0.4) respectively; and / or, in the third mixture, the ratio of the total molar amount of Ni, Fe and Mn to the molar amount of B is 1:(0.0001~0.01).

[0017] In the above technical scheme, the molar ratio of Ni, Fe and Mn in the first mixture is limited to a specific range of (0.2~0.35): (0.2~0.4): (0.2~0.4), and the ratio of the total molar amount of Ni, Fe and Mn to the molar amount of B in the third mixture is limited to a specific range of 1: (0.0001~0.01), so that each element has a more suitable mass proportion in the finally prepared positive electrode active material, thereby enabling the corresponding battery to have a higher first discharge capacity, better storage performance, cycle performance and rate performance.

[0018] In some optional embodiments, the metal element in the metal source is selected from at least one of Mg, Al, Sr, Zr, Ti and Y.

[0019] In the above technical solution, there are many types of metals used to form the inorganic metal oxide layer, which can provide more feasible implementation plans, thereby facilitating the promotion and application of the technical solution provided in the embodiment of the present application.

[0020] In some optional embodiments, the metal element in the metal source is selected from at least one of Zr and Y.

[0021] In the above technical solution, the use of the above-mentioned specific types of metal elements in the metal source is helpful for the formation of an interface film during the charging and discharging process of the corresponding battery, thereby helping to improve the storage performance and cycle performance of the corresponding battery.

[0022] In some optional embodiments, in the first stage sintering and / or the second stage sintering steps, the treatment temperature is 820-1000° C., and the treatment time is 7-12 h.

[0023] In the above technical solution, the processing temperature and time in the first stage sintering and / or the second stage sintering process are limited to specific ranges, respectively, which can provide more suitable sintering conditions to allow the raw materials to fully react.

[0024] In some optional embodiments, in the third stage sintering step, the treatment temperature is 250-500°C and the treatment time is 6-10 h; and / or, in the fourth stage sintering step, the treatment temperature is 700-900°C and the treatment time is 8-12 h.

[0025] In the above technical scheme, the processing temperature and time of the third stage sintering are limited to specific ranges, which helps to form an inorganic metal oxide layer with uniform thickness and good coating integrity; the processing temperature and time of the fourth stage sintering are limited to specific ranges, which helps to dope the B element from the surface of the material to the inside of the material.

[0026] In a third aspect, an embodiment of the present application provides a sodium ion battery, comprising a positive electrode active material provided in the embodiment of the first aspect or a positive electrode active material prepared by the preparation method provided in the embodiment of the second aspect.

[0027] In the above technical solution, the sodium ion battery includes a positive electrode active material with a specific structure. Specifically, the core includes a sodium-poor phase material with a sodium content of 0.75-0.85, and the core is coated with a first shell layer (including a sodium-rich phase material with a sodium content of 0.85-0.95) and a second shell layer in sequence, and the first shell layer is also doped with B element, wherein the sodium-poor core material enables the corresponding battery to have relatively excellent storage performance, and the coating of the first shell layer helps to improve the first discharge capacity and rate performance of the corresponding battery. The doping of B element and the coating of the second shell layer help to improve the material stability of the first shell layer, so that the corresponding battery has relatively excellent cycle performance. Therefore, the sodium ion battery prepared from the positive electrode active material can have both high first discharge capacity, relatively excellent storage performance, cycle performance and rate performance.

[0028] In a fourth aspect, an embodiment of the present application provides an electrical device, comprising a sodium ion battery as provided in the embodiment of the third aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 A schematic diagram of the structure of a positive electrode active material provided in an embodiment of the present application; Figure 2 A process flow chart of a method for preparing a positive electrode active material provided in an embodiment of the present application; Figure 3 This is an electron microscope image of the positive electrode active material in Example 1 of the present application; Figure 4 This is an electron microscope image of the positive electrode active material in Example 2 of the present application; Figure 5 This is an electron microscope image of the positive electrode active material in Comparative Example 4 of the present application; Figure 6 This is a Zr element distribution diagram of the positive electrode active material in Example 1 of the present application; Figure 7 This is a Zr element distribution diagram of the positive electrode active material in Comparative Example 6 of the present application; Figure 8is a cross-sectional view of the positive electrode active material in Example 1 of the present application; Fig. 9 for Figure 8 The content distribution result of B element in the sample; Fig.10 for Figure 8 The content distribution result of Na element in the mixture; Fig.11 This is a surface microscopic image of the positive electrode active material in Example 1 of the present application; Fig.12 for Fig.11 Content distribution result diagram of B element in the sample; Fig.13 for Fig.11 The content distribution results of Na element in the sample are shown in Figure 2.

[0031] Icon: 10 - positive electrode active material; 100 - inner core; 200 - first shell; 300 - second shell. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0033] It should be noted that “and / or” in this application, such as “Feature 1 and / or Feature 2”, refers to the three situations of “Feature 1” alone, “Feature 2” alone, or “Feature 1” plus “Feature 2”.

[0034] In addition, in the description of the present application, unless otherwise specified, the meaning of "multiple" in "one or more" refers to two or more; the range of "value a~value b" includes the two end values ​​"a" and "b", and the "unit" in "value a~value b+unit" represents the "unit" of both "value a" and "value b".

[0035] The following is a detailed description of a positive electrode active material and a preparation method thereof, a sodium ion battery and an electrical device in accordance with an embodiment of the present application.

[0036] In a first aspect, the present invention provides a positive electrode active material, including a core, a first shell layer, and a second shell layer. The core material includes: Na a1 Ni b1 Fe c1 Mn d1 O2, 0.75≤a1≤0.85; the first shell is coated outside the inner core, and the first shell is also doped with B element. The materials of the first shell include: Naa2 Ni b2 Fe c2 Mn d2 B f O2, 0.85≤a2≤0.95, and a2 is not equal to a1; the second shell layer is coated on the outside of the first shell layer, and the second shell layer is an inorganic metal oxide layer.

[0037] In the present application, the positive electrode active material has the above-mentioned specific structure, specifically, the inner core includes a sodium-poor phase material with a sodium content of 0.75~0.85, and the outer core is coated with a first shell layer (including a sodium-rich phase material with a sodium content of 0.85~0.95) and a second shell layer in sequence, and the first shell layer is also doped with B element, wherein the sodium-poor inner core material enables the corresponding battery to have relatively excellent storage performance, and the coating of the first shell layer helps to improve the first discharge capacity and rate performance of the corresponding battery, and the doping of the B element and the coating of the second shell layer help to improve the material stability of the first shell layer, so that the corresponding battery has relatively excellent cycle performance. Therefore, the sodium ion battery prepared by the positive electrode active material provided in the embodiment of the present application has both a high first discharge capacity, relatively excellent storage performance, cycle performance and rate performance.

[0038] It should be noted that for the core material, if the Na content is too low or too high, the first discharge capacity of the corresponding battery will be affected, so the Na content in the core needs to be limited to a specific range.

[0039] Similarly, for the first shell layer, if the Na content is too low or too high, the cycle performance of the corresponding battery will be affected, so the Na content in the first shell layer needs to be limited to a specific range.

[0040] As an example, the material of the inner core also satisfies: 0.20≤b1≤0.35, 0.20≤c1≤0.40, 0.20≤d1≤0.40, and b1+c1+d1=1; the material of the first shell also satisfies: 0.20≤c2≤0.40, 0.20≤d2≤0.40, 0.0001≤f≤0.01, and b2+c2+d2=1; the material of the second shell includes: Na a3 XO b3 , a3 is equal to a2, 1≤b3≤4, and X is selected from at least one of Mg, Al, Sr, Zr, Ti and Y.

[0041] In this embodiment, the material of the core and the material of the first shell layer are limited to a more suitable range, so that the corresponding battery can have a higher first discharge capacity, more excellent storage performance, cycle performance and rate performance. In addition, the metal elements other than sodium in the second shell layer are selected as the above elements, which contribute to the formation of the interface film during the charge and discharge process of the corresponding battery, thereby helping to improve the storage performance and cycle performance of the corresponding battery.

[0042] It should be noted that in the second shell, since the positive and negative valence states must be balanced, the actual value of b3 is (a3 + the positive valence value of X) / 2, that is, the molar amount of O is the sum of the positive valences divided by 2.

[0043] As an example, X is selected from at least one of Zr and Y.

[0044] In this embodiment, the element of X is selected as Zr and / or Y, which is more conducive to the formation of an interface film during the charge and discharge process of the corresponding battery, thereby being more conducive to improving the storage performance and cycle performance of the corresponding battery.

[0045] As an example, the BET of the positive electrode active material is 0.34~0.44 m 2 / g, and the Dv3 of the positive electrode active material is 2.3~3.2 μm.

[0046] In this embodiment, the BET and Dv3 of the positive electrode active material are both within a relatively suitable range, indicating that the material has a relatively suitable particle size and contains less fine powder, thereby improving the cycle performance of the battery.

[0047] As an example, in the positive electrode active material, the doping depth is greater than 0.3 μm, and the mass percentage of the B element is less than 0.005%; the doping depth is equal to 0.1 μm, and the mass percentage of the B element is greater than 0.02%.

[0048] In this embodiment, limiting the content of the B element at different doping depths within a specific range helps to further improve the material stability of the material, thereby allowing the corresponding battery to have more excellent cycle performance.

[0049] As an example, the structural diagram of the positive electrode active material 10 can be found in Figure 1 , including an inner core 100 , a first shell layer 200 coated outside the inner core 100 , and a second shell layer 300 coated outside the first shell layer 200 .

[0050] In a second aspect, an embodiment of the present application provides a method for preparing a positive electrode active material, comprising the following steps: mixing raw materials containing Ni, Fe, Mn and a first Na source to obtain a first mixture; wherein, in the first mixture, the ratio of the total molar amount of Ni, Fe and Mn to the molar amount of Na is 1:(0.75~0.85); performing a first-stage sintering on the first mixture to obtain a core; mixing the core with a second Na source to obtain a second mixture; wherein, in the second mixture, the ratio of the total molar amount of Ni, Fe and Mn to the molar amount of Na is 1:(0.85~0.95); performing a second-stage sintering on the second mixture to obtain a positive electrode material intermediate; mixing the positive electrode material intermediate, boric acid and a metal source to obtain a third mixture; performing a third-stage sintering (in order to achieve uniform coating of the inorganic metal oxide layer) and a fourth-stage sintering (in order to achieve further doping of the B element) on the third mixture in sequence, wherein the treatment temperature of the fourth-stage sintering is higher than the treatment temperature of the third-stage sintering, to obtain a positive electrode active material.

[0051] In the present application, on the one hand, in the process of preparing the positive electrode active material, the ratio of the total molar amount of Ni, Fe and Mn in the first mixture to the molar amount of Na is limited to the range of 1: (0.75~0.85), and the ratio of the total molar amount of Ni, Fe and Mn in the second mixture to the molar amount of Na is limited to the range of 1: (0.85~0.95), so as to prepare a positive electrode active material intermediate with a core-shell structure with a sodium-poor phase inside and a sodium-rich phase outside, so that the corresponding battery has relatively excellent storage performance, first discharge capacity and rate performance; at the same time, the inner core of the sodium-poor phase has a first shell layer of a sodium-rich phase (the sodium-rich phase is more active than the sodium-poor phase), which is conducive to the formation of the second shell layer in the subsequent sintering process (it is easier to form a coating layer and the formed coating layer is more uniform, thereby increasing the structural strength of the material, so that the material is not easy to form small particles in the subsequent crushing process), so that the prepared positive electrode active material has the advantage of less fine powder. On the other hand, the third mixture contains boric acid in addition to the cathode material intermediate and the metal source. With the help of the fluidity of boric acid, a relatively uniform inorganic metal oxide layer can be formed during the third stage sintering process, thereby improving the uniformity of the inorganic metal oxide layer coating the cathode material intermediate, thereby reducing the amount of alkali on the surface of the material and helping to improve the stability of the material, so that the corresponding battery has a relatively excellent cycle performance, and at the same time, the prepared cathode active material has the advantage of less fine powder; in addition, after the fourth stage sintering at a higher temperature, the B element can be further doped from the surface of the material into the material, and the further doping of the B element also helps to improve the stability of the material. Through the combined effect of the two aspects, the prepared cathode active material has the advantages of less fine powder, lower alkali on the surface of the material, and higher material stability, so that the prepared sodium ion battery has both a higher first discharge capacity, relatively excellent storage performance, cycle performance, and rate performance.

[0052] It should be noted that the form of the raw materials of Ni, Fe and Mn is not limited, for example, it can be a mixture of three raw materials containing three metal elements alone, or it can be a raw material containing three metal elements at the same time. In the embodiment of the present application, the form of a raw material containing three metal elements at the same time is taken as an example, for example, a nickel iron manganese hydroxide precursor is used as a raw material. Similarly, the type of Na source is not limited, and can be set according to the conventional selection in the field, for example, it can be Na2CO3.

[0053] As an example, in the first mixture, the molar ratios of Ni, Fe and Mn are (0.2~0.35):(0.2~0.4):(0.2~0.4); and / or, in the third mixture, the ratio of the total molar amount of Ni, Fe and Mn to the molar amount of B is 1:(0.0001~0.01).

[0054] In this embodiment, the molar ratio of Ni, Fe and Mn in the first mixture is limited to a specific range of (0.2~0.35): (0.2~0.4): (0.2~0.4), and the ratio of the total molar amount of Ni, Fe and Mn to the molar amount of B in the third mixture is limited to a specific range of 1: (0.0001~0.01), so that each element has a more suitable mass proportion in the finally prepared positive electrode active material, thereby enabling the corresponding battery to have a higher first discharge capacity, better storage performance, cycle performance and rate performance.

[0055] As an example, the metal element in the metal source is selected from at least one of Mg, Al, Sr, Zr, Ti and Y; optionally, the metal element in the metal source is selected from at least one of Zr and Y.

[0056] In this embodiment, a large number of metal types are used to form the inorganic metal oxide layer, which can provide a large number of feasible implementation plans, thereby facilitating the promotion and application of the technical solutions provided in the embodiments of the present application; in addition, the use of the above-mentioned specific types of metal elements in the metal source helps the formation of an interface film during the charging and discharging process of the corresponding battery, thereby helping to improve the storage performance and cycle performance of the corresponding battery.

[0057] As an example, in the steps of the first stage sintering and / or the second stage sintering, the processing temperature is 820~1000℃, for example but not limited to the processing temperature is any one of 820℃, 850℃, 900℃, 950℃ and 1000℃, or a range between any two of them; the processing time is 7~12 h, for example but not limited to the processing time is any one of 7 h, 8 h, 9 h, 10 h, 11 h and 12 h, or a range between any two of them.

[0058] In this embodiment, the treatment temperature and time in the first stage sintering and / or the second stage sintering process are respectively limited to specific ranges, which can provide more suitable sintering conditions to allow the raw materials to fully react.

[0059] As an example, in the third stage sintering step, the treatment temperature is 250~500℃, for example but not limited to the treatment temperature of any point value of 250℃, 300℃, 350℃, 400℃, 450℃ and 500℃, or a range value between any two of them; the treatment time is 6~10 h, for example but not limited to the treatment time of any point value of 6 h, 7 h, 8 h, 9 h and 10 h, or a range value between any two of them; and / or, in the fourth stage sintering step, the treatment temperature is 700~900℃, for example but not limited to the treatment temperature of any point value of 700℃, 750℃, 800℃, 850℃ and 900℃, or a range value between any two of them; the treatment time is 8~12 h, for example but not limited to the treatment time of any point value of 8 h, 9 h, 10 h, 11 h and 12 h, or a range value between any two of them.

[0060] In this embodiment, the processing temperature and time of the third stage sintering are limited to specific ranges, which helps to form an inorganic metal oxide layer with uniform thickness and good coating integrity; the processing temperature and time of the fourth stage sintering are limited to specific ranges, which helps to dope the B element from the surface of the material to the interior of the material.

[0061] It should be noted that any process or step not specifically described or limited in the preparation process may be arranged according to conventional selection in the art.

[0062] As an example, after the first stage sintering and before mixing with the second sodium source, the core material is further comprised of a step of crushing and screening.

[0063] As an example, after the second stage sintering and before mixing with the metal source, the intermediate material further includes the steps of crushing and screening.

[0064] As an example, after the fourth stage sintering, the steps of screening, iron removal and packaging of the positive electrode active material are also included.

[0065] As an example, the process flow chart of the preparation method of the positive electrode active material is exemplarily referred to Figure 2 .

[0066] In a third aspect, an embodiment of the present application provides a sodium ion battery, comprising a positive electrode active material provided in the embodiment of the first aspect or a positive electrode active material prepared by the preparation method provided in the embodiment of the second aspect.

[0067] In the present application, the sodium ion battery includes a positive electrode active material with a specific structure, specifically, the core includes a sodium-poor phase material with a sodium content of 0.75~0.85, and the core is coated with a first shell (including a sodium-rich phase material with a sodium content of 0.85~0.95) and a second shell in sequence, and the first shell is also doped with B element, wherein the sodium-poor core material enables the corresponding battery to have relatively excellent storage performance, the coating of the first shell helps to improve the first discharge capacity and rate performance of the corresponding battery, and the doping of the B element and the coating of the second shell help to improve the material stability of the first shell, so that the corresponding battery has relatively excellent cycle performance. Therefore, the sodium ion battery prepared from the positive electrode active material can have both a high first discharge capacity, relatively excellent storage performance, cycle performance and rate performance.

[0068] In a fourth aspect, an embodiment of the present application provides an electrical device, comprising a sodium ion battery as provided in the embodiment of the third aspect.

[0069] It should be noted that there is no limitation on the specific type of electrical equipment, and it can be adaptively adjusted according to actual needs.

[0070] The features and performance of the present application are further described in detail below in conjunction with the embodiments.

[0071] Example 1 The present invention provides a method for preparing a positive electrode active material, comprising the following steps: Add 10 kg Ni into a 50 L high-speed mixer. 0.33 Fe 0.33 Mn 0.33 (OH)2 (nickel iron manganese hydroxide precursor) and 4.83 Kg Na2CO3 (first Na source) are stirred and mixed at 800 rpm for 12 min to obtain a first mixture, wherein the ratio of the total molar amount of Ni, Fe and Mn to the molar amount of Na is 1:0.8 (referred to as the first Na ratio); the first mixture is transferred to a sagger, and then the sagger is transferred to a sintering furnace, an air atmosphere is introduced, and the temperature is increased to 950°C at 3°C / min and sintered for 10 h, and then cooled with the furnace to obtain a core.

[0072] The core material was crushed and sieved, and then the crushed material was mixed with 0.60 kg Na2CO3 (the second Na source) in a 30 L high-speed mixer at 800 rpm for 12 min to obtain a second mixture, in which the ratio of the total molar amount of Ni, Fe and Mn to the molar amount of Na was 1:0.9 (referred to as the secondary Na ratio); the second mixture was transferred to a sagger, and then the sagger was transferred to a sintering furnace, an air atmosphere was introduced, and the temperature was increased to 900°C at 3°C / min and sintered for 10 h, and then cooled with the furnace to obtain a positive electrode material intermediate.

[0073] The cathode material intermediate was crushed and sieved, and then the crushed material was mixed with 67.7 g ZrO2 and 57.4 g H3BO3 in a 30 L high mixer at 800 rpm for 12 min to obtain a third mixture, wherein the ratio of the total molar amount of Ni, Fe and Mn to the molar amount of B was 1:0.001; the third mixture was transferred to a sagger, and then the sagger was transferred to a sintering furnace, an air atmosphere was introduced, and the temperature was increased to 300°C at 3°C / min and sintered for 6 h; then the temperature was increased to 800°C at 3°C / min again and sintered for 10 h, and then cooled with the furnace. The materials after being taken out of the furnace were screened, deironed and packaged in turn to obtain the cathode active material; in the cathode active material, the core is Na 0.8 Ni 0.33 Fe 0.33 Mn 0.33 O2, the first shell is Na 0.9 Ni 0.33 Fe 0.33 Mn 0.33 B 0.001 O2, the second shell is Na 0.9 ZrO 2.45 .

[0074] Example 2 The present embodiment provides a method for preparing a positive electrode active material, which differs from the embodiment 1 only in that 10 kg Ni 0.33 Fe 0.33 Mn 0.33 (OH)2 (nickel iron manganese hydroxide precursor) and 4.53 Kg Na2CO3 (first Na source) were stirred and mixed at 800 rpm for 12 min to obtain a first mixture, in which the ratio of the total molar amount of Ni, Fe and Mn to the molar amount of Na was 1:0.75 (referred to as the first Na ratio); in the positive electrode active material, the core was Na 0.75 Ni 0.33 Fe 0.33 Mn 0.33 O2, the first shell is Na 0.85 Ni0.33 Fe 0.33 Mn 0.33 B 0.001 O2, the second shell is Na 0.85 ZrO 2.425 .

[0075] Example 3 The present embodiment provides a method for preparing a positive electrode active material, which differs from the embodiment 1 only in that 10 kg Ni 0.33 Fe 0.33 Mn 0.33 (OH)2 (nickel iron manganese hydroxide precursor) and 5.13 Kg Na2CO3 (first Na source) were stirred and mixed at 800 rpm for 12 min to obtain a first mixture, in which the ratio of the total molar amount of Ni, Fe and Mn to the molar amount of Na was 1:0.85 (referred to as the first Na ratio); in the positive electrode active material, the core was Na 0.85 Ni 0.33 Fe 0.33 Mn 0.33 O2, the first shell is Na 0.95 Ni 0.33 Fe 0.33 Mn 0.33 B 0.001 O2, the second shell is Na 0.95 ZrO 2.475 .

[0076] Example 4 The present embodiment provides a method for preparing a positive electrode active material, which differs from the embodiment 1 only in that: the core material is crushed and sieved, and then the crushed material is mixed with 0.30 kg Na2CO3 (second Na source) in a 30 L high-speed mixer at 800 rpm for 12 min to obtain a second mixed material, wherein the ratio of the total molar amount of Ni, Fe and Mn to the molar amount of Na is 1:0.85 (referred to as the secondary Na ratio); in the positive electrode active material, the core is Na 0.8 Ni 0.33 Fe 0.33 Mn 0.33 O2, the first shell is Na 0.85 Ni 0.33 Fe 0.33 Mn 0.33 B 0.001 O2, the second shell is Na 0.85 ZrO 2.425 .

[0077] Example 5 The present embodiment provides a method for preparing a positive electrode active material, which differs from the embodiment 1 only in that: the core material is crushed and sieved, and then the crushed material is mixed with 0.91 kg Na2CO3 (second Na source) in a 30 L high-speed mixer at 800 rpm for 12 min to obtain a second mixed material, wherein the ratio of the total molar amount of Ni, Fe and Mn to the molar amount of Na is 1:0.95 (referred to as the secondary Na ratio); in the positive electrode active material, the core is Na 0.8 Ni 0.33 Fe 0.33 Mn 0.33 O2, the first shell is Na 0.95 Ni 0.33 Fe 0.33 Mn 0.33 B 0.001 O2, the second shell is Na 0.95 ZrO 2.475 .

[0078] Example 6 The present embodiment provides a method for preparing a positive electrode active material, which differs from the first embodiment only in that: the positive electrode material intermediate is crushed and sieved, and then the crushed material is mixed with 63.4 g Y2O3 and 57.4 g H3BO3 in a 30L high-speed mixer at 800 rpm for 12 min to obtain a third mixed material; in the positive electrode active material, the core is Na 0.8 Ni 0.33 Fe 0.33 Mn 0.33 O2, the first shell is Na 0.9 Ni 0.33 Fe 0.33 Mn 0.33 B 0.001 O2, the second shell is Na 0.9 YO 1.95 .

[0079] Comparative Example 1 The comparative example of the present application provides a method for preparing a positive electrode active material, which differs from Example 1 only in that 10 kg Ni 0.33 Fe 0.33 Mn 0.33 (OH)2 (nickel iron manganese hydroxide precursor) and 4.23 kg Na2CO3 (first Na source) were stirred and mixed at 800 rpm for 12 min to obtain a first mixture, in which the ratio of the total molar amount of Ni, Fe and Mn to the molar amount of Na was 1:0.70 (referred to as the first Na ratio); in the positive electrode active material, the core was Na 0.7 Ni 0.33Fe 0.33 Mn 0.33 O2, the first shell is Na 0.8 Ni 0.33 Fe 0.33 Mn 0.33 B 0.001 O2, the second shell is Na 0.8 ZrO 2.4 .

[0080] Comparative Example 2 The comparative example of the present application provides a method for preparing a positive electrode active material, which differs from Example 1 only in that 10 kg Ni 0.33 Fe 0.33 Mn 0.33 (OH)2 (nickel iron manganese hydroxide precursor) and 5.43 Kg Na2CO3 (first Na source) were stirred and mixed at 800 rpm for 12 min to obtain a first mixture, in which the ratio of the total molar amount of Ni, Fe and Mn to the molar amount of Na was 1:0.90 (referred to as the first Na ratio); in the positive electrode active material, the core was Na 0.9 Ni 0.33 Fe 0.33 Mn 0.33 O2, the first shell is Na 1.0 Ni 0.33 Fe 0.33 Mn 0.33 B 0.001 O2, the second shell is Na 1.0 ZrO 2.5 .

[0081] Comparative Example 3 The comparative example of the present application provides a method for preparing a positive electrode active material, which differs from Example 1 only in that: the core material is crushed and sieved, and then the crushed material is mixed with 1.21 kg Na2CO3 (a second Na source) in a 30 L high-speed mixer at 800 rpm for 12 min to obtain a second mixed material, wherein the ratio of the total molar amount of Ni, Fe and Mn to the molar amount of Na is 1:1 (referred to as the secondary Na ratio); in the positive electrode active material, the core is Na 0.8 Ni 0.33 Fe 0.33 Mn 0.33 O2, the first shell is Na 1.0 Ni 0.33 Fe 0.33 Mn 0.33 B 0.001 O2, the second shell is Na 1.0 ZrO 2. 5 .

[0082] Comparative Example 4 The comparative example of the present application provides a method for preparing a positive electrode active material, which differs from Example 1 only in that: except that the second Na source is not added, the process steps are the same as those of Example 1; in the positive electrode active material, the core is Na 0.8 Ni 0.33 Fe 0.33 Mn 0.33 O2, the first shell is Na 0.8 Ni 0.33 Fe 0.33 Mn 0.33 B 0.001 O2 (i.e., the amount of Na in the first shell is the same as that in the core), and the second shell is Na 0.8 ZrO 2.4 .

[0083] Comparative Example 5 The comparative example of the present application provides a method for preparing a positive electrode active material, which differs from Example 1 only in that: except that ZrO2 is not added, the process steps are the same as those of Example 1, that is, there is no second shell layer outside the first shell layer; in the positive electrode active material, the core is Na 0.8 Ni 0.33 Fe 0.33 Mn 0.33 O2, the first shell is Na 0.9 Ni 0.33 Fe 0.33 Mn 0.33 B 0.001 O2, no second shell.

[0084] Comparative Example 6 The comparative example of the present application provides a method for preparing a positive electrode active material, which differs from Example 1 only in that: except for not adding boric acid, the process steps are the same as those of Example 1, that is, there is no B doping in the first shell layer, and the coating uniformity of the second shell layer cannot be improved; in the positive electrode active material, the core is Na 0.8 Ni 0.33 Fe 0.33 Mn 0.33 O2, the first shell is Na 0.9 Ni 0.33 Fe 0.33 Mn 0.33 O2, the second shell is Na 0.9 ZrO 2.45 .

[0085] Comparative Example 7 The comparative example of the present application provides a method for preparing a positive electrode active material, which differs from Example 1 only in that: the fourth stage sintering is not performed, that is, the B element is not further doped; in the positive electrode active material, the core is Na0.8 Ni 0.33 Fe 0.33 Mn 0.33 O2, the first shell is Na 0.9 Ni 0.33 Fe 0.33 Mn 0.33 O2, the second shell is Na 0.95 Zr 0.75 B 0.25 O 2.35 .

[0086] In order to better understand the differences between the various embodiments and comparative examples, a summary description is given below in the form of a table, and specific reference may be made to Table 1.

[0087] Table 1

[0088] Test Example 1 Material performance testing Test method: The positive active materials prepared in Examples 1 to 6 and Comparative Examples 1 to 7 were numbered respectively, and then the BET, Dv3, carbonate concentration measured in water, and hydroxide concentration measured in ethanol of each sample were tested; then each positive active material was assembled into a battery, and then the battery's first discharge capacity, 21-day 45°C storage retention rate, 21-day 45°C storage recovery rate, 45°C cycle 200 times capacity retention rate, and rate performance were tested. Finally, the various test data results are statistically summarized in Table 2.

[0089] Among them, the testing steps of BET are as follows: A sample tube with a bulb of 3 / 8 inch and a length of 12 mm was used, and the sample volume was 2 / 3 of the bulb. Pretreatment was performed before measurement, with a degassing temperature of 200°C and a degassing time of 2 h, followed by cooling and weighing; cooling to room temperature, the weighing accuracy was controlled at 0.0001 g, the adsorbent was high-purity 99.999% nitrogen, the adsorption pressure deviation was 0.05 mmHg, the equilibrium time was 5 s, and the relative pressure points (P / P0) were selected as 0.05, 0.1, 0.15, 0.2, 0.25, and 0.30, the numerical linearity was >99.9%, and the reading value retained three significant digits.

[0090] The test steps for Dv3 are as follows: The Malvern 3000 equipment was used with a detection angle of 0~144°. The sample was first ultrasonically dispersed in water. The dispersion method was to add the sample (sample amount 0.15 g) + 1 dropper of 10% sodium hexametaphosphate + water to 20 mL in a 50 mL beaker (external ultrasound for 5 minutes, intensity 60%), the external ultrasound intensity was 53 KHz, and the dispersed solution was added to water for particle size testing. The speed of the agitator / pump was 3000 rpm, the analysis mode was the general mode, the shading degree was 8~12%, the test time was 10 s, and then the particle size value of 3% by volume was read in the equipment.

[0091] The steps for testing carbonate concentration in water are as follows: Weigh 2 g of sample and add it to 100 ml of pure water, stir for 30 min, filter 50 ml with filter paper, then transfer 10 ml, and use 0.05 mol / L HCl solution to determine the endpoint according to potentiometric titration to obtain CO3 2- Content, that is, Na2CO3 content.

[0092] The test steps for measuring the hydroxide concentration of ethanol are as follows: Weigh 2 g of sample and add it to 100 ml of ethanol, stir for 60 min, filter 50 ml with filter paper, then transfer 10 ml, use 0.05 mol / L HCl solution, and determine the endpoint by potentiometric titration to obtain OH - The content is the NaOH content.

[0093] The steps for assembling the battery are as follows: Each sample was used as the positive electrode material, and the positive electrode material, acetylene black and binder PVDF were added to NMP in a mass ratio of 90%:5%:5% to mix and prepare the positive electrode slurry; the positive electrode slurry was evenly coated on aluminum foil, vacuum baked at 80°C, pressed and cut to obtain a positive electrode sheet with a diameter of 14 mm, a pure sodium sheet with a diameter of 16 mm was used as the negative electrode sheet, Tianci ENA-18 was used as the electrolyte, and a PP / PE / PP composite separator was used to assemble into a button battery in a glove box filled with argon.

[0094] Among them, the test steps of the first discharge capacity of the battery are as follows: At 25°C, the battery was charged to 4.0 V at a constant current of 0.5 C, then charged at a constant voltage until the current was less than or equal to 0.01 mA, then allowed to stand for 5 minutes, and then discharged to 2.0 V at a constant current of 0.5 C, then allowed to stand for 5 minutes. This was a charge and discharge cycle, and the discharge capacity was recorded as the discharge capacity of the battery in the first cycle.

[0095] The test steps for 21-day 45°C storage retention rate are as follows: First, fully charge the battery and then test the battery discharge capacity T1. Then store the fully charged battery at 45°C for 21 days and then test the battery discharge capacity T2. Calculate the retention rate using the formula = T2 / T1*100%.

[0096] The test steps for the 21-day 45°C storage recovery rate are as follows: First, fully charge the battery and then test the battery discharge capacity T1. Then, store the fully charged battery at 45°C for 21 days. After discharging the battery, fully charge it again and discharge it, test the discharge capacity T3, and calculate the recovery rate. The formula is = T3 / T1*100%.

[0097] The test steps for capacity retention after 200 cycles at 45°C are as follows: At 45°C, the battery cell is first charged to 4.0V at a constant current of 1C, then further charged to a current of 0.05C at a constant voltage of 4.0V, and discharged to 2.0V at a constant current of 1 / 3C. This is a charge and discharge cycle process, and the discharge capacity this time is the discharge capacity of the first cycle. The battery cell is subjected to multiple cycle charge and discharge tests in the above manner, and the discharge capacity of the 200th cycle is detected, and the capacity retention rate of the battery cell after the cycle is calculated by the following formula. The capacity retention rate of the battery after 200 cycles (%) = [discharge capacity of the 200th cycle / discharge capacity of the first cycle] × 100%.

[0098] The test steps for rate performance are as follows: The above button battery was tested using the BlueDian battery test system CT2001A at 25°C with a constant voltage cutoff current of 0.05C. The specific steps are as follows: Step 1: Charge at 0.1C to the cut-off voltage, let stand for 2 minutes, discharge at 0.1C to the termination voltage, let stand for 2 minutes.

[0099] Step 2: Charge at 0.2C to the cut-off voltage, and discharge at 0.2C to the termination voltage.

[0100] Step 3: Charge at 0.5C to the cut-off voltage, and discharge at 0.5C to the termination voltage.

[0101] Step 4: Charge at 0.5C to the cut-off voltage and discharge at 1C to the termination voltage.

[0102] Step 5: Charge at 0.5C to the cut-off voltage and discharge at 2C to the termination voltage.

[0103] Step 6: Charge at 0.5C to the cut-off voltage and discharge at 3C to the termination voltage.

[0104] The rate performance data is the ratio of 3C discharge capacity to 0.1C discharge capacity.

[0105] Table 2

[0106] Referring to Table 2, it can be seen from the test results of Examples 1 to 6 and Comparative Examples 1 to 7 that the positive electrode active material is prepared according to the preparation process provided in the embodiments of the present application, and the prepared positive electrode active material has the advantages of less fine powder, lower alkali content on the surface of the material and higher material stability, so that the corresponding battery can have a higher first discharge capacity, better storage performance, cycle performance and rate performance.

[0107] From the test results of Examples 1 to 3 and Comparative Examples 1 to 2, it can be seen that the Na content in the core is limited to the range of 0.75 to 0.85, so that the corresponding battery has a higher first discharge capacity, better storage performance, cycle performance and rate performance.

[0108] From the test results of Examples 1, 4 and 5 and Comparative Example 3, it can be seen that the Na content in the first shell is limited to the range of 0.85~0.95, so that the corresponding battery has a higher first discharge capacity, better storage performance, cycle performance and rate performance.

[0109] From the test results of Examples 1, 4 and 5 and Comparative Example 4, it can be seen that the sodium-poor phase has a first shell layer of a sodium-rich phase outside the inner core, so that the corresponding battery has a higher first discharge capacity, more excellent storage performance, cycle performance and rate performance; at the same time, it also helps the formation of the second shell layer in the subsequent sintering process (it is easier to form a coating layer and the formed coating layer is more uniform, thereby increasing the structural strength of the material, making it less likely for the material to form small particles in the subsequent crushing process), thereby making the prepared positive electrode active material have the advantage of less fine powder.

[0110] It can be seen from the test results of Example 1 and Comparative Example 5 that coating the inorganic metal oxide layer (i.e., the second shell layer) outside the first shell layer can reduce the amount of alkali on the surface of the material and also help to improve the stability of the material, so that the corresponding battery can have a higher first discharge capacity, relatively excellent storage performance, cycle performance and rate performance.

[0111] It can be seen from the test results of Example 1 and Comparative Example 6 that adding boric acid in the process of forming the inorganic metal oxide layer helps to improve the coating uniformity of the inorganic metal oxide layer, thereby reducing the alkalinity of the material surface, and thus enabling the corresponding battery to have a higher initial discharge capacity, relatively excellent storage performance, cycle performance and rate performance; at the same time, it can also enable the prepared positive electrode active material to have the advantage of less fine powder.

[0112] From the test results of Example 1 and Comparative Example 7, it can be seen that the doping of B element in the first shell layer helps to improve the problems of excessive fine powder in the material and excessive alkali on the surface of the material, and also helps to improve the stability of the material, so that the corresponding battery can have a higher first discharge capacity, relatively excellent storage performance, cycle performance and rate performance.

[0113] Test Example 2 Microstructural testing of materials Test method: The positive electrode active materials prepared in Examples 1-2 and Comparative Example 4 were numbered respectively, and then the microstructure of each sample was characterized using an electron microscope.

[0114] See also Figure 3~Figure 5 From the test results, it can be seen that secondary Na supplementation is carried out during the preparation process to form a core-shell structure with different Na contents (corresponding to the inner core and the first shell outside the inner core). The prepared material contains less fine powder, which can effectively improve the fine powder problem of the material.

[0115] Test Example 3 Material coating uniformity test Test method: The positive electrode active materials prepared in Example 1 and Comparative Example 6 were numbered respectively, and then the distribution of the Zr element in each sample was characterized using an electron microscope.

[0116] See also Figure 6 and Figure 7 It can be seen that adding boric acid during the formation of the inorganic metal oxide layer helps to improve the coating uniformity of the inorganic metal oxide layer. Figure 6 and Figure 7 (The scale is 20 nm) It can be seen that the Zr element is distributed in the area of ​​about 0~50 nm, indicating that the thickness of the second shell layer in the positive electrode active material is roughly around 50 nm.

[0117] Test Example 4 Distribution of B and Na elements in positive electrode active materials Test method: The material of Example 1 was used as the test object and ion milling was performed using a Gatan 697 Ilion II device. The outlet pressure of high-purity argon was controlled at 0.18 MPa and the pressure in the sample chamber was less than 5×10 -6Torr, the left and right gun angles were controlled at 0 degrees, and the ion beam energy was 5 keV. After grinding, EDS measurement was performed using Hitachi Regulus 8100 / SU 8010, with the test voltage controlled at 1KV, the test current at 10 μA, and the magnification of 18 K for point scanning. Ni, Fe, Mn, Zr, B, and Na were selected as the main elements, and the element ratio was automatically calculated according to the selected points at different positions.

[0118] See also Figure 8 (in, Figure 8 The scale in the figure is 3 μm, and each grid represents 0.3 μm. Figure 1 , 2 , 3, 4, 5 are greater than 0.3 μm from the surface, and the spectrum Figure 6 The depth from the surface is within 0.1~0.3 μm, where the spectrum Figure 7 , 8 , 11, 12 The depth from the surface is within 0.1 μm but above 50 nm) Fig. 9 , Fig.11 (B content test on the surface of the positive electrode active material in Example 1) and Fig.12 It can be seen that in the positive electrode active material, the doping depth is greater than 0.3 μm, and the mass percentage of B element is less than 0.005%, which is assumed to contain no B, that is, the area with a depth greater than 0.3 μm from the material surface corresponds to the core of the positive electrode active material; the doping depth is equal to 0.1 μm, the mass percentage of B element is greater than 0.02%, corresponding to the part of the first shell outside the core; the mass percentage of B element on the material surface is less than 0.005%, which is assumed to contain no B, corresponding to the part of the second shell outside the first shell, indicating that after high-temperature calcination, B enters the first shell from the second shell.

[0119] See also Figure 8 (in, Figure 8 The scale in the figure is 3 μm, and each grid represents 0.3 μm. Figure 1 , 2 , 3, 4, 5 are greater than 0.3 μm from the surface, and the spectrum Figure 6 The depth from the surface is within 0.1~0.3 μm, where the spectrum Figure 7 , 8 , 11, 12 The depth from the surface is within 0.1 μm but above 50 nm) Fig.10 , Fig.11 and Fig.13It can be seen that in the positive electrode active material, the molar ratio of the Na element in the area with a depth greater than 0.3 μm from the material surface is 0.75~0.85, corresponding to the core of the positive electrode active material; the molar ratio of the Na element in the area with a depth of 50 nm~0.3 μm from the material surface is 0.85~0.95, corresponding to the first shell of the positive electrode active material; the molar ratio of the Na element on the material surface is 0.85~0.95, corresponding to the second shell of the positive electrode active material.

[0120] Combined with Figure 6~Figure 13 The results show that, based on the molar ratio of B content and Na, the area above 0.3 μm from the surface of the material is the core of the positive electrode active material, corresponding to the structural formula: Na a1 Ni b1 Fe c1 Mn d1 O2, 0.75≤a1≤0.85; the area 50 nm~0.3 μm from the surface of the material is the first shell of the positive electrode active material, corresponding to the structural formula: Na a2 Ni b2 Fe c2 Mn d2 B f O2, 0.85≤a2≤0.95, and a2 is not equal to a1; the area within 50 nm from the surface is the second shell of the positive electrode active material, corresponding to the structural formula: Na a3 XO b3 , a3 equals a2, 1≤b3≤4.

[0121] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.

Claims

1. A positive electrode active material, characterized in that: include: The core material includes: Na a1 Ni b1 Fe c1 Mn d1 O2, 0.75≤a1≤0.85; The first shell layer is coated on the outside of the core, and the first shell layer is also doped with B element. The material of the first shell layer includes: Na a2 Ni b2 Fe c2 Mn d2 B f O2, 0.85≤a2≤0.95, and a2 is not equal to a1; The second shell layer is coated on the outside of the first shell layer, and the second shell layer is an inorganic metal oxide layer.

2. The positive electrode active material according to claim 1, characterized in that The material of the inner core also satisfies: 0.20≤b1≤0.35, 0.20≤c1≤0.40, 0.20≤d1≤0.40, and b1+c1+d1=1; The material of the first shell layer also satisfies: 0.20≤c2≤0.40, 0.20≤d2≤0.40, 0.0001≤f≤0.01, and b2+c2+d2=1; The material of the second shell layer includes: Na a3 XO b3 , a3 is equal to a2, 1≤b3≤4, and X is selected from at least one of Mg, Al, Sr, Zr, Ti and Y.

3. The positive electrode active material according to claim 2, characterized in that The X is selected from at least one of Zr and Y.

4. The positive electrode active material according to claim 1, characterized in that The BET of the positive electrode active material is 0.34-0.44 m 2 / g, and the Dv3 of the positive electrode active material is 2.3~3.2 μm.

5. The positive electrode active material according to any one of claims 1 to 4, characterized in that In the positive electrode active material, when the doping depth is greater than 0.3 μm, the mass percentage of the B element is less than 0.005%; when the doping depth is equal to 0.1 μm, the mass percentage of the B element is greater than 0.02%.

6. A method for preparing a positive electrode active material, characterized in that: The following steps are involved: Mixing raw materials containing Ni, Fe, Mn and a first Na source to obtain a first mixed material; wherein, in the first mixed material, the ratio of the total molar amount of Ni, Fe and Mn to the molar amount of Na is 1:(0.75-0.85); performing a first-stage sintering on the first mixed material to obtain a core; The core is mixed with a second Na source to obtain a second mixed material; wherein, in the second mixed material, the ratio of the total molar amount of Ni, Fe and Mn to the molar amount of Na is 1:(0.85-0.95); the second mixed material is subjected to a second stage sintering to obtain a positive electrode material intermediate; The positive electrode material intermediate, boric acid and metal source are mixed to obtain a third mixture; the third mixture is subjected to third stage sintering and fourth stage sintering in sequence, wherein the treatment temperature of the fourth stage sintering is higher than the treatment temperature of the third stage sintering, to obtain a positive electrode active material.

7. The preparation method according to claim 6, characterized in that: In the first mixed material, the molar ratios of Ni, Fe and Mn are (0.2-0.35): (0.2-0.4): (0.2-0.4); And / or, in the third mixed material, the ratio of the total molar amount of Ni, Fe and Mn to the molar amount of B is 1:(0.0001~0.01).

8. The preparation method according to claim 6, characterized in that: The metal element in the metal source is selected from at least one of Mg, Al, Sr, Zr, Ti and Y.

9. The preparation method according to claim 8, characterized in that: The metal element in the metal source is selected from at least one of Zr and Y.

10. The preparation method according to claim 6, characterized in that In the first stage sintering and / or the second stage sintering steps, the treatment temperature is 820-1000° C. and the treatment time is 7-12 h.

11. The preparation method according to claim 6, characterized in that In the third stage sintering step, the treatment temperature is 250-500°C and the treatment time is 6-10 hours; And / or, in the fourth stage sintering step, the treatment temperature is 700-900° C. and the treatment time is 8-12 h.

12. A sodium ion battery, characterized in that: The invention comprises the positive electrode active material according to any one of claims 1 to 5 or the positive electrode active material prepared by the preparation method according to any one of claims 6 to 11.

13. An electrical equipment, characterized in that: Including the sodium ion battery as described in claim 12.

Citation Information

Patent Citations

  • Sodium ion battery positive electrode material, preparation method thereof and sodium ion battery

    CN111403729A

  • Layered positive electrode material of sodium-ion battery and application of layered positive electrode material

    CN115528226A

  • Layered sodium ion battery positive electrode material, preparation method thereof and sodium ion battery

    CN116190619A

  • Anion-cation co-doped and coated sodium ion battery positive electrode material and preparation method thereof

    CN116417590A

  • Positive electrode material and preparation method and application thereof

    CN117080424A

Cited By

  • Lithium ion secondary battery, preparation method and electric device

    CN119890415A

  • Lithium-ion secondary battery, method of manufacturing, and electric device

    CN119890415B

  • Preparation method of sodium ion battery cell with ultralow temperature performance

    CN120674611A